Letter (copy) - Squance, W. J. R.
012b-0072-001 Telegraphic Address "Aslocobrom, Haver London" Telephone No HAMPSTEAD 6300 Associated Society of Locomotive Engineers and Firemen Trade Union No. 348 APPROVED SOCIETY NO. 253. 9 Arkwright Road Hampstead London N.W.3 W.J.R. Squance General Secretary W.P.Allen Assistant General Secretary NOTE. For each subject — a separate letter. The Rt. Hon. Neville Chamberlain, P.C., M.P. Prime Minister, 10. Downing Street, Whitehall, S.W.1. 18th January, 1939. My dear Prime Minister. My Executive Committee, who are now in session, are very concerned about the situation in Spain and after very careful consideration of the recent happenings and possibilities in that unfortunate Country they have concluded that the domination of Spain and the Mediterranean by the Fascist Powers - who are actively intervening in Spain by the supply of armed forces and all paraphernalia of modern warfare - threatens the peace of the world. Animated by deep feelings to preserve the fundamental and essential human issues of International Peace, Freedom and Democracy, which they believe are now gravely threatened by the recent events and possibilities in Spain, they have adopted a resolution requesting me to approach you, and if possible, arrange an interview to enable them to submit their viewpoint upon this matter of urgency, and to advance reasons for the removal of the embargo on arms for Republican Spain, the opening of the French frontiers and the rendering of all such other things within the realm of International Law and Social Justice in their hour of need. They also desire me to say that in their solemn judgment this policy is in keeping with International Justice and Equity, and will ultimately prove to be a sound foundation for a just and lasting peace. Yours respectfully W.J.R. Squance GENERAL SECRETARY. T.U.C. 292/946/12b/72